(untitled) (Universal International Scientific Journal, 2026)
The paper examines the theoretical and methodological aspects of studying the physiological and biochemical resilience of foreign basil (Ocimum basilicum L.) genotypes to the natural factors of the Surkhandarya region. The necessity of a comprehensive analysis of photosynthetic pigments and essential oil composition is substantiated for the selection of promising forms for the perfume industry.